Grape Juice Concentrate Protects Rat Liver Against Cadmium Intoxication: Histopathology, Cytochrome C and Metalloproteinases Expression - de Moura, C. F. G.; Ribeiro, F. A. P.; Handan, B. A.; Aguiar, O.; Oshima, C. T. F.; Ribeiro, D. A. (Drug Research, 2016)
The aim of this study was to investigate if grape juice concentrate is able to protect rat liver against cadmium toxicity. For this purpose, histopathological analysis, cytochrome C expression and immunoexpresssion of metalloproteinases (MMP) 2 and 9 were investigated. A total of 15 Wistar rats weighing 250 g on the average, and 8 weeks age were distributed into 3 groups (n=5), as follows: Control group (non-treated group, CTRL); Cadmium group (Cd) and grape juice concentrate group (Cd+GJ). Histopathological analysis revealed that liver from animals treated with grape juice concentrate improved tissue degeneration induced by cadmium intoxication. Animals intoxicated with cadmium and treated with grape juice concentrate showed higher cytochrome C gene expression in liver cells. No significant statistically differences (p>0.05) were found to MMP 2 and 9 immunoexpression between groups. Taken together, our results demonstrate that grape juice concentrate is able to prevent tissue degeneration in rat liver as a result of increasing apoptosis.
Keywords: grape juice concentrate; cadmium; rat; cytochrome C; metalloproteinases